Not International Relations' 'mare nostrum': On the divergence between the Mediterranean and the discipline of International Relations. Issue 2 (15th March 2021) - Kuru, Deniz
ABSTRACT: This study analyzes the (dis)connections between the Mediterranean and the discipline of International Relations (IR) by focusing on their interactions from two distinct but complementary perspectives. First, a comparative analysis of leading academic IR journals both from the most active IR scholarly communities (American/global, European, British) and across the northern/European Mediterranean region (Spain, France, Italy, Croatia, and Turkey) looks to what extent topics related to the Mediterranean have found a place in these publications. Second, it offers a more disciplinary analysis that considers the reasons of IR's lacking engagement with the Mediterranean, pointing to the discipline's historical and sociological development that hindered a greater role for this significant region in IR theories and empirics. The study concludes by discussing the possibility of a Mediterranean IR theory that would consider the region's distinct world historical role while pointing to the constraints faced by such an alternative theoretical framework.